Socio-Environmental Impact Assessment of Oleaginous Crops for Biodiesel Production in Brazil - Geraldo Stachetti Rodrigues; Izilda Aparecida Rodrigues; Cláudio Cesar de Almeida Buschinelli; Marcos Antônio Vieira Ligo; Adriana Marlene Moreno Pires; Rosa T. S. Frighetto; Luiz José Maria Irias (Journal of Technology Management & Innovation, 2007)
Socio-environmental impact assessments were carried out on oleaginous crops for biodiesel production under the context of expanding demand in five regions of Brazil. The study brought together representatives of the main interest groups in Delphi-type workshops. Major impacts are related with increases in demand for inputs, resources, and energy, with potential risks on water quality and habitat conservation. In some instances, management practices may improve soil quality, favoring habitats recovery. Crop intensification is expected to bring important contributions for farmer capacitation, income generation and sources diversity, as well as improved management and administration. Institutional especially designed local productive arrangements offer the best options for fostering sustainable development and avoiding environmental degradation risks, under the scenario of expanding demand on oleaginous crops for biodiesel production.